Tragedy and Democracy - Bensussan, Gérard (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This contribution aims to think the complex relationship between two Greek inventions, democracy and tragedy, detecting in it an insurmountable paradox. Three propositions are articulated: 1) tragedy is political; 2) the dialectic that pretends to philosophically grasp its meanings is democratic in its principle of mediation; 3) the tragic remains beyond the dialectic. Democratic politics, in the modern sense, would like to cushion death. It enshrines the effort inscribed in finitude to elude death, to postpone it, to stop thinking about it. Its vocation is profoundly antitragic. However, it is and remains tragic, because it faces its own destinal and impossible task to put an end to the tragic
Keywords: Tragedy; Democracy; Dialectics; Death